Features of a new identity from the experience of women in neighborhoods - Santisteban, Fryné (1985)
The role that society assigns to women profoundly marks their lives and their identity, defining their tasks, their world of relationships and their central concerns. The overload of your routine and the time you demand, make your home the main space in which your life unfolds. Her position as a housewife and mother of a family delimits her world of relationships: her partner, her children, other relatives and a few neighbors constitute her most important ties. Her work as a mother and her special dedication to others also mark her own aspirations, which she does not dare to acknowledge.